Geographical analysis of voter apathy in presidential elections between 1999 and 2011 in Nigeria (2015)
Correlates and predictors of the spatiotemporal pattern of voter apathy in presidential elections were analyzed for all the states in Nigeria between 1999 and 2011, using data from the National Bureau of Statistics. The Moran Index (Local and Global), analysis of variance, and geographical weighted regression were used in understanding the spatiotemporal patterns and drivers of voter apathy. There were statistically significant temporal (F = 4.811, P ≤ .05) and spatial (F = 8.133 P ≤ .05) variations, and spatial dependency in voter apathy. Men’s population size, expenditures on number of higher institutions of learning, expenditures on household goods and education were main predictors of voter apathy.